CC-Qual: A holistic scale to assess customer perceptions of service quality of collaborative consumption services. (December 2019) - Marimon, Frederic; Llach, Josep; Alonso-Almeida, Mar; Mas-Machuca, Marta
Highlights: It validates a scale to assess the perceived quality of collaborative consumption. Second order construct that includes platform quality, peer provider and other customers' interaction dimensions are considered. Quality relies on the web encounter experience and the supplier contact experience. Abstract: The paper defines and validates a scale—CC-Qual—to assess the quality of services provided through a Collaborative Consumption (CC) model. The authors have borrowed a set of items arranged in eight dimensions from the literature on CC. A panel of selected practitioners (seven CEOs of CC companies) assisted in the design of the questionnaire, which was launched in June 2018. A sample of 127 questionnaires was used for exploratory factor analysis. A second sample of 301 users was used for confirmatory analysis using EQS 6.4 software. A scale of 21 items gathered under five dimensions is proposed. Accordingly, the perceived quality in CC is composed of five dimensions: three of them related to the interaction with the platform ("site organization", "platform responsiveness and agility" and "legal protection and trustworthiness"), another related to the perceived quality of the peer service supplier ("peer service provider") and the last one to assess the encounters with other consumers and with the person who provides the service ("social interaction"). This study provides a useful measure for the assessment of the perceived quality of CC services, regardless of the activity sector. This instrument might assist managers for both assessing and benchmarking. The instrument also provides independent and reliable information for customers.